Optomagnonics in Dispersive Media: Magnon-Photon Coupling Enhancement at the Epsilon-near-Zero Frequency - Bittencourt, V. A. S. V.; Liberal, I.; Kusminskiy, S. Viola (Physical Review Letters, 2022)
Reaching strong light-matter coupling in solid-state systems has long been pursued for the implementation of scalable quantum devices. Here, we put forward a system based on a magnetized epsilon-near zero (ENZ) medium, and we show that strong coupling between magnetic excitations (magnons) and light can be achieved close to the ENZ frequency due to a drastic enhancement of the magneto-optical response. We adopt a phenomenological approach to quantize the electromagnetic field inside a dispersive magnetic medium in order to obtain the frequency-dependent coupling between magnons and photons. We predict that, in the epsilon-near-zero regime, the single-magnon single-photon coupling can be comparable to the magnon frequency for a small magnetic volume and perfect mode overlap. For state-of-the-art illustrative values, this would correspond to achieving the single-magnon strong coupling regime, where the coupling rate is larger than all the decay rates. Finally, we show that the nonlinear energy spectrum intrinsic to this coupling regime can be probed via the characteristic multiple magnon sidebands in the photon power spectrum.
CRIS-Team WoS Importer:2022-06-17